2017
DOI: 10.1063/1.4973862
|View full text |Cite
|
Sign up to set email alerts
|

Combined electrical transport and capacitance spectroscopy of a MoS2-LiNbO3 field effect transistor

Abstract: We have measured both the current-voltage (I SD -V GS ) and capacitance-voltage (C-V GS ) characteristics of a MoS 2 − LiNbO 3 field effect transistor. From the measured capacitance we calculate the electron surface density and show that its gate voltage dependence follows the theoretical prediction resulting from the twodimensional free electron model. This model allows us to fit the measured I SD -V GS characteristics over the entire range of V GS . Combining this experimental result with the measured curren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In recent years, many experimental efforts have been focused on integrating 2D MX 2 materials with ferroelectrics due to their switchable electric polarization and the high dielectric constant. Hereinafter, we take MoS 2 as an example.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many experimental efforts have been focused on integrating 2D MX 2 materials with ferroelectrics due to their switchable electric polarization and the high dielectric constant. Hereinafter, we take MoS 2 as an example.…”
Section: Introductionmentioning
confidence: 99%
“…For chemical vapor deposition of MoS 2 onto LiNbO 3 (0001) polar surfaces, the polarization direction of the ferroelectric substrate showed a remarkable effect on the growth and transport properties of the MoS 2 films . As demonstrated in refs , , the monolayer MoS 2 /LiNbO 3 hybrid structure can be used for the field-effect transistor (FET) and the FET-electro-acoustic device. By transferring the MoS 2 flakes on top of the epitaxial PbZr 0.2 Ti 0.8 O 3 (PZT) single crystalline film, Lu et al reported that the back-gated MoS 2 /PZT FET shows excellent current–voltage behavior directly controlled by ferroelectric polarization.…”
Section: Introductionmentioning
confidence: 99%
“…The transfer of the QDs onto a strong piezoelectric substrate such as LiNbO 3 , with K 2 » 5%, could help enhance the coupling between a semiconductor heterostructure and the SAW field [4]. However, direct epitaxial growth of semiconductors on LiNbO 3 has so far only be achieved for two-dimensional transition metal dichalcogenides [14,30]. Thus, for most semiconductors, such hybrid devices can be fabricated by epitaxial lift-off and transfer of the QD membrane on a LiNbO 3 SAW-chip [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, C-V measurements in small-area 2D materials are very sensitive and always suffer from several difficulties. 5,[38][39][40][41] A systematic study on the parasitic capacitance resulting from an n + -Si/SiO2 substrate and the channel resistance effect in C-V is necessary. Theoretically, quantum capacitance in monolayer MoS2 has been clarified in our previous work.…”
Section: Introductionmentioning
confidence: 99%
“…Although C – V measurements are quite informative, blindly applying this method established based on a bulk metal–oxide–semiconductor (MOS) FET/capacitor to an ACCU-FET can lead to incorrect conclusions. Experimentally, C – V measurements in small-area 2D materials are very sensitive and always suffer from several difficulties. , A systematic study on the parasitic capacitance resulting from an n + -Si/SiO 2 substrate and the channel resistance effect in C – V is necessary. Theoretically, quantum capacitance in monolayer MoS 2 has been clarified in our previous work .…”
Section: Introductionmentioning
confidence: 99%